Gene expression changes in the tyrosine metabolic pathway regulate caste-specific cuticular pigmentation of termites. (July 2016) - Masuoka, Yudai; Maekawa, Kiyoto
Abstract: In social insects, all castes have characteristic phenotypes suitable for their own tasks and to engage in social behavior. The acquisition of caste-specific phenotypes was a key event in the course of social insect evolution. However, understanding of the genetic basis and the developmental mechanisms that produce these phenotypes is still very limited. In particular, termites normally possess more than two castes with specific phenotypes (i.e. workers, soldiers, and reproductives), but proximate developmental mechanisms are far from being fully understood. In this study, we focused on the pigmentation of the cuticle as a model trait for caste-specific phenotypes, during the molts of each caste; workers, soldiers, presoldiers (intermediate stage of soldiers), and alates (primary reproductives) in Zootermopsis nevadensis . Expression patterns of cuticular tanning genes (members of the tyrosine metabolic pathway) were different among each molt, and high expression levels of several "key genes" were observed during each caste differentiation. For the differentiation of castes with well-tanned cuticles (i.e. soldiers and alates), all focal genes except DDC in the former were highly expressed. On the other hand, high expression levels of yellow and aaNAT were observed during worker and presoldier molts, respectively, but most other genes in the pathway were expressed at low levels. RNA interference (RNAi) of these key genes affected caste-specific cuticular pigmentation, leading to soldiers with yellowish-white heads and pigmented mandibular tips, presoldiers with partly pigmented head cuticles, and alates with the yellow head capsules. These results suggest that the pigmentation of caste-specific cuticles is achieved by the regulation of gene expression in the tyrosine metabolic pathway. Graphical abstract: Highlights: Expression of genes acting in the tyrosine metabolic pathway was analyzed during termite caste differentiation. Various crucial genes showed specific expression during differentiation of each caste. Knockdown of key genes inhibited caste-specific cuticular pigmentation.